In-situ surface study on the mechanism of high-strain-rate superplasticity in an Al–Cu–Li alloy - Zhixin Shen; Guotong Zou; Yu Dong; Yujia Zhang; Lingying Ye (Journal of Materials Research and Technology, 2024)
An elongation of 880 % was obtained at a high initial strain rate of 1 × 10−2 s−1 at 470 °C in an Al–Cu–Li alloy produced by traditional thermomechanical-processing. The high-strain-rate superplastic deformation mechanisms during the whole deformation process were studied by SEM, EBSD, and FIB techniques. High-resolution surface studies employing focused ion beams reveal that grain boundary sliding accounts for up to 70 % of the overall strain. Furthermore, this phenomenon consistently maintains a high level, with a minimum value of 56 %, throughout the entire deformation process. Meanwhile, diffusion creep plays an accommodating role and stimulates the formation of striated bands.